Scientific Discovery and Inference: Between the Lab and Field in Biology. - Grosholz, Emily; Posteraro, Tano; Grigas, Alex (Topoi: An International Review of Philosophy, 2020)
An adequate account of how inferences and discoveries are made in modern biology is a difficult prospect for a philosopher. Do we really deduce conclusions from Darwin's principles? Once Darwinian biology is integrated with molecular biology, can we deduce the organism from its DNA? What does induction look like in an era where data sets are often too large to be processed by a human being? What is the role of abductive explanatory claims that try to define the biological individual in relation to the microbiome with which it may be associated, or to revise the notion of evolution when the interaction of organism and environment comes to seem much more complex than earlier generations imagined. How should we evaluate "origins of life" experiments conducted in the laboratory, where chemistry shifts to biology and we try to recreate early conditions on earth to which we have no empirical access? How are the carefully controlled conditions in the lab to be brought into productive relationship with the messy, contingent outdoor work of biologists in the field, studying crabs or eelgrass at the edge of the Pacific Ocean, or prairie plants at the end of woods, on the plains of the Midwest. To answer these questions, I sent my graduate student Tano Posteraro to work with Ted Grosholz, a marine biologist at the University of California / Davis, and my undergraduate student Alex Grigas to work with Ruth Geyer Shaw, a population geneticist at the University of Minnesota. They came back with complex and interesting answers to these questions.